A Cross-Cultural Associative Study of Concepts (Education, Freedom, Happiness) - Orazbekova, Indira (Journal of Education Culture and Society, 2025)
Aim. The study aims at conducting a free associative experiment to define fragments of conceptual worldviews of Kazakh and Afghan students aged 18-24 on human concepts (Education, Freedom, Happiness). The relevance of the study is determined by presenting the cross-comparison analysis of the hierarchy of constituent parts (nucleus and periphery) of concepts.Methods. The association experiment was conducted through a questionnaire and the data was processed by Word Cloud technology. The research methods involved in the study were interpretation, comparison, statistical analysis.Results. The research underscores that concept is not a stable, rigid category, and it changes under the influence of ongoing transformations in the world. The results of the associative test indicate that the concept constituents comprise basic, universal associations and culture-specific, individual patterns. The experiment results testify that the surrounding environment, for example, economic or socio-political changes, shape world perceptions of a particular cultural community.Conclusion. The cross-comparison study provides new viewpoints on the hierarchy of the nuclear and peripheral constituent elements within conceptual frameworks of Kazakh and Afghan worldviews.